Hypoxia-driven sarcoplasmic/endoplasmic reticulum calcium ATPase 2 (SERCA2) downregulation depends on low-density lipoprotein receptor-related protein 1 (LRP1)-signalling in cardiomyocytes. (August 2015) - Revuelta-López, Elena; Cal, Roi; Herraiz-Martínez, Adela; de Gonzalo-Calvo, David; Nasarre, Laura; Roura, Santiago; Gálvez-Montón, Carolina; Bayes-Genis, Antoni; Badimon, Lina; Hove-Madsen, Leif; Llorente-Cortés, Vicenta
Abstract: The maintenance of sarcoplasmic reticulum Ca 2 + ATPase (SERCA2) activity is crucial for cardiac function and SERCA2 is dramatically reduced in the heart exposed to hypoxic/ischemic conditions. Previous work from our group showed that hypoxia upregulates the phosphorylated form of the Ca 2 + -dependent nonreceptor protein tyrosine kinase (PTK) proline-rich tyrosine kinase 2 (pPyk2) protein levels in a low-density lipoprotein receptor-related protein (LRP1)-dependent manner. Pyk2 in turn may modulate SERCA2 in cardiomyocytes although this remains controversial. We therefore aimed to investigate the role of LRP1 on hypoxia-induced SERCA2 depletion in cardiomyocytes and to establish LRP1 signalling mechanisms involved. Western blot analysis showed that hypoxia reduced SERCA2 concomitantly with a sustained increase in LRP1 and pPyk2 protein levels in HL-1 cardiomyocytes. By impairing hypoxia-induced Pyk2 phosphorylation and HIF-1α accumulation, LRP1 deficiency prevented SERCA2 depletion and reduction of the sarcoplasmic reticulum calcium content in cardiomyocytes. Moreover, the inhibition of Pyk2 phosphorylation (with the Src-family inhibitor PP2) or the specific silencing of Pyk2 (with siRNA-anti Pyk2) preserved low HIF-1α and high SERCA2 levels in HL-1 cardiomyocytes exposed to hypoxia. We determined that the LRP1/Pyk2 axis represses SERCA2 mRNA expression via HIF-1α since HIF-1α overexpression abolished the protective effect of LRP1 deficiency on SERCA2 depletion. Our findings show a crucial role of LRP1/Pyk2/HIF-1α in hypoxia-induced cardiomyocyte SERCA2 downregulation, a pathophysiological process closely associated with heart failure. Graphical abstract: Highlights: LRP1 mediates the upregulatory effect of hypoxia on Pyk2 phosphorylation in cardiomyocytes. LRP1/pPyk2 axis mediates SERCA2 downregulation in cardiomyocytes. LRP1 is essential for HIF-1α accumulation that plays a major role on hypoxia-induced SERCA2 downregulation in cardiomyocytes.